Managing psychosocial issues among HLI students during crises - Azlan, Haffiezhah An-Nadiah; Syed Esa, Syed Ahmad Muhajir Alhaddad; Zakariya, Hafiz; Kasturi, Taufik (Akademi Kepimpinan Pendidikan Tinggi (AKEPT) and AbdulHamid AbuSulayman KIRKHS, IIUM, 2023)
Crisis management has become an essential function of HLI. This chapter thus discusses the management of psychosocial issues among HLI students during a crisis.